SIMULASI DAN ANALISIS DAMPAK PLTS SKALA BESAR DAN BESS TERHADAP SUSUT DAYA SISTEM KELISTRIKAN NUSA PENIDA - Caesar, B; Kumara, INS; Sukerayasa, IW; Giriantari, IAD; Setiawan, IN; Ariastina, WG (Jurnal SPEKTRUM, 2024)
Nusa Penida island is one of the famous tourist destinations in the province of Bali. Increased tourism activities on Nusa Penida island has led to an increase in demand for electricity. In response, PT. PLN (Persero) has made great efforts to improve the quality of the power supply system in Nusa Penida to meet the increasing energy demand. As a concrete step, PT. PLN (Persero) has established a 4,2 MWp Solar Power Plant (PLTS) and a 1,84 MWh Battery Energy Storage System (BESS) to provide electrical energy to Nusa Penida. This research aims to analyze the impact of PLTS and BESS on power losses in the electrical power supply system in Nusa Penida. The electrical system of Nusa Penida simulated using the demo version of the power system dynamics simulation software. The simulation electrical system of Nusa Penida conducted under four different conditions. The results of the simulation show that both PLTS and BESS have a positive impact on power loss of electrical system in Nusa Penida.